Economic Profitability and Carbon Stock Potential of Cereals and Pulses Under Harar and Aonla Based Agroforestry Systems in The Low Hill Zone of Himachal Pradesh - Bhatia, Avinash Kumar; Sharma, Kamal; Pant, K. S.; Singh, Samanpreet; Prakash, Prem; Kumar, Parveen; Saakshi; Sharma, Harish (International Journal of Economic Plants, 2022)
Practicing wheat-maize cropping system by the farmers of Himachal Pradesh is less economical viable as compared to pulses. Besides this, pulses have high potential of soil improvement through nitrogen fixation. Hence, the experiment was premeditated to evaluate the carbon stock potential and economic profitability of cereals and pulses under Harar and Aonla based agroforestry systems in the low hill zone of Himachal Pradesh. The experiment was conducted with nine treatment combinations with four replications in RBD. Highest biomass (77.80 t ha-1) and carbon stock (38.05 t ha-1) were recorded under maize+Harar. In term of economics, maximum gross returns (80,471.49 Rs. ha-1) were obtained for maize+Aonla yet, the maximum net returns (42,684.40 Rs. ha-1) and BC ratio (2.14) were found for mash+Aonla.